Novel strategy for selection of monoclonal antibodies against highly conserved antigens: phage library panning against ephrin-B2 displayed on yeast. - Xiaoling Gu; Yogindra Vedvyas; Xiaoyue Chen; Tanwi Kaushik; Chang-Il Hwang; Xuebo Hu; Alexander Y Nikitin; Moonsoo M Jin (PLoS ONE, 2012)
Ephrin-B2 is predominately expressed in endothelium of arterial origin, involved in developmental angiogenesis and neovasculature formation through its interaction with EphB4. Despite its importance in physiology and pathological conditions, it has been challenging to produce monoclonal antibodies against ephrin-B2 due to its high conservation in sequence throughout human and rodents. Using a novel approach for antibody selection by panning a phage library of human antibody against antigens displayed in yeast, we have isolated high affinity antibodies against ephrin-B2. The function of one high affinity binder (named as 'EC8') was manifested in its ability to inhibit ephrin-B2 interaction with EphB4, to cross-react with murine ephrin-B2, and to induce internalization into ephrin-B2 expressing cells. EC8 was also compatible with immunoprecipitation and detection of ephrin-B2 expression in the tissue after standard chemical fixation procedure. Consistent with previous reports on ephrin-B2 induction in some epithelial tumors and tumor-associated vasculatures, EC8 specifically detected ephrin-B2 in tumors as well as the vasculature within and outside of the tumors. We envision that monoclonal antibody developed in this study may be used as a reagent to probe ephrin-B2 distribution in normal as well as in pathological conditions and to antagonize ephrin-B2 interaction with EphB4 for basic science and therapeutic applications.